ANALYSIS OF QUALITY CONTROL EFFECTIVENESS THROUGH QUALITY STANDARDIZATION AUDITS AS A MEASURE TO ADDRESS PRODUCT NON-CONFORMANCE (CASE STUDY AT PT. X) - Dina Dwi Oktavia Rini; Dewi Elok Oktaviana Sari (Antis Publisher, 2026)
Objective: This study examines quality control effectiveness at PT. X upper production line, where non-conformance rates remain high, primarily due to recurring missing felt cases that cause shoes to fall below thickness standards. Method: Using a qualitative approach (in-depth interviews and direct observation with QC team, supervisor, and operator). Results: The study finds that audit procedures are structured yet operator compliance is situational. Three root causes are identified: excessive production targets, limited operator awareness of work-step consequences, and a QC-operator quality perception gap. CAPA actions are executed but lack verification mechanisms, allowing recurring defects. Novelty: Quality improvement demands transformed audit practices, closed CAPA cycles, and quality-driven incentive systems.